Design parameters for installing Rainwater Harvesting System (RWHS) for mosques: a systematic literature review analysis / Kazrena Nalia Mat Daud ... [et al.] - Mat Daud, Kazrena Nalia; Che Ahmad, Asmalia; Hassan Naziri, Ahmad Faiz; Zainonabidin, Azman (2021)
The function of Rainwater Harvesting System (RWHS) has been expanded tremendously throughout the years with the latest equipment and current technology. Multiple buildings, such as government buildings and others have been equipped with this system. Previous studies have also proven that collected rainwater can be used for non-potable and potable water. In Malaysia, based on the available rainfall supply, there is a tremendous potential of RWHS usage, especially for buildings that use water the most, such as mosques. Nevertheless, the current RWHS design guidelines and practice in Malaysia regarding implementation in mosques, either existing buildings or newly constructed ones are inadequate. RWHS components are already available in the market, but since all buildings have different water usage and multiple setbacks, a study is needed in order to single out a specific usage of RWHS for mosques. Thus, a systematic literature review (SLR) was carried out to identify the design parameters of RWHS suitable for mosques. A total of 25 articles were abstracted from Scopus, Science Direct, and Google Scholar databases for the SLR. The result shows five design parameters that can be employed to suitably implement RWHS in mosques.